2009
DOI: 10.1097/wnf.0b013e31817e559b
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Extended Release (OROS MPH) for the Treatment of Antidepressant-Related Sexual Dysfunction in Patients With Treatment-Resistant Depression

Abstract: There are limited data to indicate effective treatment strategies for antidepressant-related sexual dysfunction, in particular for patients with treatment-resistant major depression. We subanalyzed our published data whether augmentation with methylphenidate extended release (OROS MPH) improved sexual dysfunction associated with antidepressants in patients with treatment-resistant major depression. The primary efficacy measure was the change in Arizona Sexual Experiences Survey (ASEX) from baseline to end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A 4-week, double-blind, placebo controlled trial was conducted by Pae and colleagues [46], but they failed to detect a significant benefit of applying methylphenidate extended-release (OROS MPH) to improve antidepressantrelated sexual dysfunction in patients with TRD.…”
Section: Level 3: Methylphenidatementioning
confidence: 99%
“…A 4-week, double-blind, placebo controlled trial was conducted by Pae and colleagues [46], but they failed to detect a significant benefit of applying methylphenidate extended-release (OROS MPH) to improve antidepressantrelated sexual dysfunction in patients with TRD.…”
Section: Level 3: Methylphenidatementioning
confidence: 99%
“…Acute doses of psychostimulants appear more efficacious in the treatment of SSRI-induced sexual dysfunction and depression than chronic doses, as tolerance develops rapidly, thus causing symptoms of sexual dysfunction to return. Women taking methylphenidate in two of the case reports [26,27] reported a return of symptoms within 2.5 and 9 weeks. In some cases of psychostimulant treatment, increases in dose were warranted in order for participants to sustain positive effects.…”
Section: Stimulantsmentioning
confidence: 99%
“…In fact, one woman discontinued the medication, methylphenidate, because the sexual stimulation was so intense [26]. Men, on the other hand, experienced arousal with stronger erections, but did not expe-rience the same persistent arousal [26]. Pae et al conducted a double-blind, randomized controlled trial examining the efficacy of extended-release methylphenidate in the treatment of sexual dysfunction associated with antidepressant use [26].…”
Section: Stimulantsmentioning
confidence: 99%
“…This drug fits to the piperidine class of compounds and increases the levels of dopamine and noradrenaline in the brain through reuptake inhibition of the monoamine transporters [11]. The main urinary metabolite is a de-esterified product, ritalinic acid (RA), which accounts for 80% of the dosage and has a half-life of about 8 h [11]. Reviews over pharmacy databases and treatment studies have shown that the incidences of medication discontinuation or non-adherence is between 13.2% and 64% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Methylphenidate (MPH) is a psychostimulant drug approved primarily for the treatment of attention deficit hyperactivity disorder (ADHD) and narcolepsy [11]. This drug fits to the piperidine class of compounds and increases the levels of dopamine and noradrenaline in the brain through reuptake inhibition of the monoamine transporters [11]. The main urinary metabolite is a de-esterified product, ritalinic acid (RA), which accounts for 80% of the dosage and has a half-life of about 8 h [11].…”
Section: Introductionmentioning
confidence: 99%